Urban Multi-scale Environmental Predictor (UMEP): An integrated tool for city-based climate services. (January 2018) - Lindberg, Fredrik; Grimmond, C.S.B.; Gabey, Andrew; Huang, Bei; Kent, Christoph W.; Sun, Ting; Theeuwes, Natalie E.; Järvi, Leena; Ward, Helen C.; Capel-Timms, I.; Chang, Yuanyong; Jonsson, Per; et al.
Abstract: UMEP (Urban Multi-scale Environmental Predictor), a city-based climate service tool, combines models and tools essential for climate simulations. Applications are presented to illustrate UMEP's potential in the identification of heat waves and cold waves; the impact of green infrastructure on runoff; the effects of buildings on human thermal stress; solar energy production; and the impact of human activities on heat emissions. UMEP has broad utility for applications related to outdoor thermal comfort, wind, urban energy consumption and climate change mitigation. It includes tools to enable users to input atmospheric and surface data from multiple sources, to characterise the urban environment, to prepare meteorological data for use in cities, to undertake simulations and consider scenarios, and to compare and visualise different combinations of climate indicators. An open-source tool, UMEP is designed to be easily updated as new data and tools are developed, and to be accessible to researchers, decision-makers and practitioners. Highlights: A GIS-based climate planning tool for researcher and practitioners is presented. UMEP has broad utility for applications related to e.g. climate change mitigation. Applications are presented to illustrate UMEP's potential.